DETERMINAN PROFITABILITAS PADA SEKTOR PERBANKAN YANG TERDAFTAR DI INDEKS LQ45 BURSA EFEK INDONESIA PERIODE 2015- 2020 - Rissa Raevita Fariha; Susanti Usman (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2020)
Banking financial institutions have an important role in the economicdevelopment of a country. The purpose of this study was to determine the factorsthat affect profitability in the banking sector listed on the LQ45 Indonesia StockExchange for the 2015-2020 period. This research method uses quantitative datatypes and secondary data sources obtained from the website www.idx.com andrelated company websites. The sample was selected using purposive samplingmethod in order to obtain 5 companies in the banking sector with a period of 6years. The analytical method used in this study is multiple linear regressionprocessed using SPSS version 25. The results of this study indicate that the factorsof the Audit Committee, Institutional Ownership Structure, and Leverage affect profitability. Meanwhile, the Board of Commissioners, Board of Directors,Managerial Ownership Structure, and Company Size have not been able to provetheir influence on Profitability. Simultaneously the Board of Commissioners,Board of Directors, Audit Committee, Institutional Ownership Structure,Managerial Ownership Structure, Company Size, and Leverage affectProfitability